Legal consequences of the postponed gubernatorial election in Central Kalimantan (January 27, 2016) - Ridho, M. Rosyid (Journal of Law Science, 2025)
The exercise of people's sovereignty in a direct democracy is realized through general elections, including Regional Head Elections (Pilkada). This study aims to analyze the legal implications of the postponed gubernatorial election of Central Kalimantan, which was eventually held on January 27, 2016. The method used is normative juridical analysis by reviewing relevant laws and regulations, as well as decisions issued by the General Elections Commission (KPU). Data were obtained from legal documents and regulations governing the implementation of Pilkada. The findings indicate that the Indonesian KPU and the Provincial KPU of Central Kalimantan committed unlawful acts by failing to conduct the election on the predetermined date and by scheduling a follow-up election without a solid legal basis. It is concluded that these actions are inconsistent with the prevailing legal provisions and have legal implications for the legitimacy of the election in Central Kalimantan.